Percepción de los docentes sobre la aplicación del plan individual de ajustes razonables, en educación básica (2019)
The present project seeks to deepen the analysis, application, and relevance of the individual plan of reasonable adjustments in the academic improvement of children with special educational needs. This is related with the curriculum and the pedagogical processes, framed in the rationalist-deductive paradigm, with a mixed approach and with a type of descriptive design. A sample consisting of classroom and support teachers, students, parents and principals of the school Vista Hermosa de Soledad was taken as a source of analysis, to which surveys and interviews were applied, and all of them validated by experts. After processing and making the analysis of the information, it was possible to identify the gaps in the dissemination and application of the PIAR and it is seen as a weakness that all the responsibility lies on the support teachers; the interest shown by teachers in appropriating the processes of inclusion stands out. In the school, PIAR sensitization processes that allow the progress of academic processes must be generated. Finally, the project allowed to reveal the guidelines for the application of the PIAR in the institution.